Post-(De)colonial Thinking and the Other Half of Western Modernity: Abū Hayyān al-Tawḥīdī’s Humanism in the Renaissance of Islamc - Jaouad El Habbouch (تجسير)
The postmodern condition constitutes an extremely important threshold from which we can productively engage with the modern episteme. However, what has been identified as a new historical rupture in postmodern theory does not mark the end of modernity as the new world system is both reminiscent of the colonial past and symptomatic of its neocolonial impulse. This entanglement between the colonial past and the neo-colonial present urges us to foster new epistemic sovereignties and cognitive paradigms in conversation with the postcolonial and decolonial visions of the world. If the postcolonial perspective involves the critical reconsideration of the Eurocentric legacy of modernity as a form of “cultural hegemony” and “epistemological bias”, the decolonial perspective seeks to delink from “the universal fictions of modernity” and subvert the legacy of Western “global linear thinking”. Informed by this critical consciousness, the aim of this paper is twofold; the first is to reconsider the problematic relationship between Islam and modernity from a postcolonial standpoint, while the second emphasizes the importance of the decolonial option in our endeavor to shift the geography of reasoning from Western cannons of thought into non-European traditions of knowledge. The article explores Abū Ḥayyān al-Tawḥīdī’s philosophical spirit as an instance of early Arab-Islamic humanism. Informed by postcolonial critical consciousness, I believe that the need to revisit the Muslim intellectual legacy of the “Golden Age” is vitally important to subvert the modern imperial episteme and reenergize hope in the ability of non-Eurocentric traditions of knowledge to foster new cognitive paradigms and canons of thought.